Linguistic critical practice among early Arab grammarians and its impact on the development of Arabic grammar - aaouar, moussa (El Omda in Linguistics and Discourse Analysis, 2022)
Le fondement d'une critique linguistique objective de la grammaire arabe ancienne nécessite le retour à la pratique critique des grammairiens anciens arabes, pour but de ressusciter cette grammaire dans une nouvelle forme qui s'adapte à l'époque contemporaine, et mettre en place une théorie critique linguistique arabe basée sur des normes strictes lesquelles le critique peut s'appuyer dans son approche critique linguistique de la grammaire arabe ancienne, et éviter d'obtenir des résultats non scientifique car ces critères doivent êtres provenus de la pensée critique arabe non de celle de la pensée occidentale qui peut faire du mal plus que du bien. The foundation of an objective linguistic critique of ancient Arabic grammar, requires a return to the critical practice of ancient Arabic grammarians, with the aim of resuscitating this grammar in a new form that adapts to contemporary times, and to establish a Arabic linguistic critical theory based on strict standards which the critic can rely on in his linguistic critical approach to ancient Arabic grammar, and avoid obtaining unscientific results because these criteria must be derived from Arabic critical thinking not from that Western thought that can do more harm than good.